1997
DOI: 10.1016/s0092-8674(00)81858-9
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis NPR1 Gene That Controls Systemic Acquired Resistance Encodes a Novel Protein Containing Ankyrin Repeats

Abstract: The Arabidopsis NPR1 gene controls the onset of systemic acquired resistance (SAR), a plant immunity, to a broad spectrum of pathogens that is normally established after a primary exposure to avirulent pathogens. Mutants with defects in NPR1 fail to respond to various SAR-inducing treatments, displaying little expression of pathogenesis-related (PR) genes and exhibiting increased susceptibility to infections. NPR1 was cloned using a map-based approach and was found to encode a novel protein containing ankyrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
1,205
0
20

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,390 publications
(1,259 citation statements)
references
References 36 publications
34
1,205
0
20
Order By: Relevance
“…SON1 is another F-box protein that has been implicated in plant defense signaling [58]. The son1 (suppressor of nim1-1) mutant was isolated from genetic screens for suppressors of non-inducible immunity1 (nim1, also referred as npr1), of which the corresponding wild-type gene is a key positive regulator of Arabidopsis SAR [59,60]. The son1 mutant displays SAR-independent, constitutive resistance against both the virulent oomycete Peronospora parasitica and the bacterial pathogen Pseudomonas syringae pv tomato strain DC3000, indicating that SON1-mediated ubiquitination negatively regulate plant defense.…”
Section: Members Of the Ubiquitination System Are Implicated In Plantmentioning
confidence: 99%
“…SON1 is another F-box protein that has been implicated in plant defense signaling [58]. The son1 (suppressor of nim1-1) mutant was isolated from genetic screens for suppressors of non-inducible immunity1 (nim1, also referred as npr1), of which the corresponding wild-type gene is a key positive regulator of Arabidopsis SAR [59,60]. The son1 mutant displays SAR-independent, constitutive resistance against both the virulent oomycete Peronospora parasitica and the bacterial pathogen Pseudomonas syringae pv tomato strain DC3000, indicating that SON1-mediated ubiquitination negatively regulate plant defense.…”
Section: Members Of the Ubiquitination System Are Implicated In Plantmentioning
confidence: 99%
“…Some contain single base substitutions that translate into single amino acid changes, whereas others harbor premature stop codons or frameshift mutations. We selected three NPR1 mutants, npr1-1 , nim1-2 , and npr1-2 , that harbor single amino acid replacements and are unambiguously compromised in their ability to mount SAR (Cao et al, 1997;Ryals et al, 1997), and we tested, using the yeast two-hybrid system, their capacity to interact with TGA2 and TGA3. One of these factors, TGA2, has already been shown not to interact with NPR1-1 and NPR1-2 (Zhang et al, 1999).…”
Section: Npr1 Mutant Proteins That Fail To Mount Sar In the Plant Faimentioning
confidence: 99%
“…Genetic analyses have established that NPR1 acts downstream of SA in the SAR signal transduction pathway (Cao et al, 1994;Delaney et al, 1995) and downstream of jasmonate and ethylene in the ISR signaling pathway . The NPR1 gene has recently been isolated and predicted to encode a protein containing ankyrin-like repeats (Cao et al, 1997;Ryals et al, 1997), which is a motif known to be responsible for mediating protein-protein interactions (Sedgwick and Smerdon, 1999). It has been proposed that NPR1 possesses extensive sequence conservation with the mammalian protein I B ␣ and that it may represent the plant homolog of I B ␣ (Ryals et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…PR genes are activated in the SAR pathway but not in the ISR pathway, which suggests that the associated defence responses are differentially regulated by NPR1 depending on the signalling pathway that is activated upstream of NPR1. Sequence analysis revealed that NPR1 contains a functionally important ankyrin-repeat domain that might be involved in protein-protein interactions 47,48 . Binding of pathway-specific proteins to NPR1 might therefore account for the separation of the SAR and ISR pathways downstream of NPR1.…”
Section: Systemic Resistance Induced By Non-pathogenic Rhizobacteriamentioning
confidence: 99%